Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.15448/1980-6523.2016.1.19521
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestations in chronic kidney failure patients

Abstract: Objective: Chronic kidney failure (CKF) is a progressive deterioration of the kidneys. The goal of this study was to analyze the oral manifestation of CKF in a sample of hemodialysis and transplanted patients. Methods: Eighty-three records of patients treated in the Pro-Renal Foundation in Curitiba, Brazil were used. The records were separated in four groups: Transplanted Men (TM = 14), Transplanted Women (TW = 18), Men in Hemodialysis (MHD = 28) and Women in Hemodialysis (WHD = 23). Information about oral and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Failure to do so can lead to the onset of infectious diseases thatinterfere with the treatment and/or even delaykidneytransplant [9]. The saliva, which plays a major role in digesting food and in preserving the integrity oforal tissues, can be negatively affected inpatients with kidney failure.However, few studies have evaluated salivarychanges and composition in patients undergoing HD [10,11].Research has shown that fluid intake restriction, use of different types of drugs, systemic disorders and radiation therapy are specific risk factors for changes insalivary pH and flow [12].…”
Section: Introductionmentioning
confidence: 99%
“…Failure to do so can lead to the onset of infectious diseases thatinterfere with the treatment and/or even delaykidneytransplant [9]. The saliva, which plays a major role in digesting food and in preserving the integrity oforal tissues, can be negatively affected inpatients with kidney failure.However, few studies have evaluated salivarychanges and composition in patients undergoing HD [10,11].Research has shown that fluid intake restriction, use of different types of drugs, systemic disorders and radiation therapy are specific risk factors for changes insalivary pH and flow [12].…”
Section: Introductionmentioning
confidence: 99%